Role of autophagy in intervertebral disc degeneration. Issue 2 (17th November 2021) - Kritschil, Rebecca; Scott, Melanie; Sowa, Gwendolyn; Vo, Nam
Abstract: Intervertebral disc degeneration (IDD) is a leading contributor to low back pain. The intervertebral disc (IVD) is composed of three tissue types: the central gelatinous nucleus pulposus (NP) tissue, the surrounding annulus fibrosus (AF) tissue, and the inferior and superior cartilage endplates. The IVD microenvironment is hypoxic, acidic, hyperosmotic, and low in nutrients because it is mostly avascular. The cellular processes that underlie IDD initiation and progression are still poorly understood. Specifically, a lack of understanding regarding NP cell metabolism and physiology hinders the development of effective therapeutics to treat IDD patients. Autophagy is a vital intracellular degradation process that removes damaged organelles, misfolded proteins, and intracellular pathogens and recycles the degraded components for cellular energy and function. NP cells have adapted to survive within their harsh tissue microenvironment using processes that are largely unknown, and we postulate autophagy is one of these undiscovered mechanisms. In this review, we describe unique features of the IVD tissue, review how physiological stressors impact autophagy in NP cells in vitro, survey the current understanding of autophagy regulation in the IVD, and assess the relationship between autophagy and IDD. Published studies confirm autophagy markers are present in IVD tissue, and IVD cells can regulate autophagy in response to cellular stressors in vitro. However, data are still lacking to determine the exact mechanisms regulating autophagy in IVD cells. More in‐depth research is needed to establish whether autophagy is necessary to maintain IVD cell health and validate autophagy as a relevant therapeutic target for treating IDD. Abstract : As autophagy gets upregulated in cells under stress, it is reasoned that intervertebral disc (IVD) cells employ autophagy as a survival mechanism within their harsh tissue microenvironment. In this review, we describe unique features of the IVD tissue, review how physiological stressors impact autophagy in IVD cells in vitro, survey the current understanding of autophagy regulation in the IVD, and assess the relationship between autophagy and intervertebral disc degeneration (IDD). Published studies confirm autophagy markers are present in IVD tissue and that IVD cells can regulate autophagy in response to cellular stressors in vitro.